On the size-Ramsey number of grid graphs. (6th September 2021) - Clemens, Dennis; Miralaei, Meysam; Reding, Damian; Schacht, Mathias; Taraz, Anusch
Abstract: The size-Ramsey number of a graph F is the smallest number of edges in a graph G with the Ramsey property for F, that is, with the property that any 2-colouring of the edges of G contains a monochromatic copy of F . We prove that the size-Ramsey number of the grid graph on n × n vertices is bounded from above by n 3+o(1) .